“Elaboración de vino con mosto concentrado de uva borgoña negra (vitis labrusca)” - Celis Escudero, Francisco Rafael (2001)
The present paper is briented to elaborating of wine from grape variety Borgoña negra (Vitis labrusca), through grape must concentration. The grape variety Borgoña negra, is cultivated in the Districts of San Antonio of Cumbaza and Tarapoto Province of San Martin, it is a variety that has low contents of soluble solids, elevated acidity, good aroma and color. This study comprehendes three stages, the first where was detennine to find optimum temperature of concentration, which has essayed treatments at 50, 60, 70 and 80 ºC, grape must was concentrated to 40 ºBrix. It has evaluated physical chemical characteristics at the beginning and final of concentration, and sensorial analysis, throuhg affective test (5 points hedonical scale method) that it detennined the best concentration temperature at 50 ºC. Second stage, was essayed to elaborating of wine utilizing concentrated juice of 30, 35 and 40 ºBrix. The concentrated at 35 and 40 ºBrix were standardized to 30 ºBrix, which, have realized mixtures with grape juice non concentrated (35 ºBrix more grape juice non concentrated, 40 ºBri,'{ more grape juice non concentrated), squeezed grape (35 ºBrix more squeezed grape, 40 ºBri,'{ more squeezed grape) and grape husk (35 ºBrix more grape Q_usk and 40 ºBrix more grape husk). During all process of elaborating wine, were evaluated physical chemical characteristics and a sensorial analysis, by means of affective test ( 5 points hedonical scale method), that detennined obtaining a best wine using concentrated grape must mixture at 40 ºBrix which was standardized to 30 ºBti"' utilizing squeezed grape. And fmal stage, comprehends to elaborating experimental wine (standardized grape must at 30 ºBrix with concentrated grape juice at 40 ºBrix more squeezed grape), and a testifier's wine (elaborated with addition of granulated sugar) containing a soluble solids concentration at 30 ºBrix, evaluating their physical chemical characteristics during process The experimental and testifiers wine were put in storage during 90 days, evaluating physical chenúcal and microbiological characteristics, that there were little variations of them. The storage period is over was carried out a sensorial analysis through difference test (Ranking method), with object to detennine its acceptability, concluding that experimental wine has major acceptance than testifier and commercial wine.